Syringe and needle size, syringe type, vacuum generation, and needle control in aspiration procedures - Haseler, Luke; Sibbitt, R.; Sibbitt, W.; Michael, A.; Gasparovic, C.; Bankhurst, A. (Springer-Verlag New York, LLC, 2011)
Purpose: Syringes are used for diagnostic fluid aspiration and fine-needle aspiration biopsy in interventional procedures. We determined the benefits, disadvantages, and patient safety implications of syringe and needle size on vacuum generation, hand force requirements, biopsy/fluid yield, and needle control during aspiration procedures. Materials and Methods: Different sizes (1, 3, 5, 10, and 20 ml) of the conventional syringe and aspirating mechanical safety syringe, the reciprocating procedure device, were studied. Twenty operators performed aspiration procedures with the following outcomes measured: (1) vacuum (torr), (2) time to vacuum (s), (3) hand force to generate vacuum (torr-cm 2 ), (4) operator difficulty during aspiration, (5) biopsy yield (mg), and (6) operator control of the needle tip position (mm). Results: Vacuum increased tissue biopsy yield at all needle diameters ( P < 0.002). Twenty-milliliter syringes achieved a vacuum of -517 torr but required far more strength to aspirate, and resulted in significant loss of needle control (P < 0.002). The 10-ml syringe generated only 15% less vacuum (-435 torr) than the 20-ml device and required much less hand strength. The mechanical syringe generated identical vacuum at all syringe sizes with less hand force (P < 0.002) and provided significantly enhanced needle control (P < 0.002). Conclusions: To optimize patient safety and control of the needle, and to maximize fluid and tissue yield during aspiration procedures, a two-handed technique and the smallest syringe size adequate for the procedure should be used. If precise needle control or one-handed operation is required, a mechanical safety syringe should be considered. Â© 2010 Springer Science+Business Media, LLC and the Cardiovascular and Interventional Radiological Society of Europe (CIRSE).